Nonthermal Irreversible Electroporation to the Esophagus: Evaluation of Acute and Long‐Term Pathological Effects in a Rabbit Model - Yue Song (Wiley, 2021)
Background Esophageal ulceration and fistula are severe complications of pulmonary vein isolation using thermal ablation. Nonthermal irreversible electroporation (NTIRE) is a promising new technology for pulmonary vein isolation in patients with atrial fibrillation. NTIRE ablation technology has been used to treat atrial fibrillation; however, the effects of NTIRE on esophageal tissue have not been clearly described. Methods and Results A typical NTIRE electrical protocol was directly applied to esophagi in 84 New Zealand rabbits. Finite element modeling and histological analysis with 120 slices were used to analyze electric field intensity distribution and subsequent tissue changes. A parameter combination of 2000 V/cm multiplied by 90 pulses output is determined to be an effective ablation parameters combination. Within 16 weeks after ablation, no obvious lumen stenosis, epithelial erythema, erosion, ulcer, or fistula was observed in the esophageal tissue. NTIRE effectively results in esophageal cell ablation to death, and subsequently, signs of recovery gradually appear: creeping replacement and regeneration of epithelial basal cells, repair and regeneration of muscle cells, structural remodeling of the muscle layer, and finally the restoration of clear anatomical structures in all layers. Conclusions Monophasic, bipolar NTIRE delivered using plate electrodes in a novel esophageal injury model demonstrates no histopathologic changes to the esophagus at 16 weeks. Data of this study suggest that electroporation ablation is a safe modality for pulsed electroporation ablation near the esophagus.